1997
DOI: 10.1063/1.120080
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and superfluorescence of rare-earth chelate-doped graded index polymer optical fibers

Abstract: Rare-earth chelate-doped graded index (GI) polymer optical fibers (POF) are proposed and fabricated. The attenuation loss was measured to be 0.4 dB/m at 650 nm for a GI POF doped with 1 wt % of europium (Eu) chelate. Lifetime shortening and spectral narrowing verified the occurrence of superfluorescence at 614 nm in the Eu chelate-doped GI POF pumped with xenon flashlamps. The demonstration of superfluorescence shows that rare-earth chelate-doped GI POFs are appealing as optical amplifiers and superfluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 4 publications
2
42
0
1
Order By: Relevance
“…Finally the interested reader is referred to a number reports and review papers on rare-earth doped polymer fiber lasers and amplifiers [265][266][267].…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…Finally the interested reader is referred to a number reports and review papers on rare-earth doped polymer fiber lasers and amplifiers [265][266][267].…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…19,20,39,40 However, it has been found that multimode fiber has lower efficiency than that of single mode fiber. Under this circumstance, a program concerning SCPOF doped with rare earth has been established after our previous work on multimode POF amplifie.…”
Section: Preparation Of Scpof Preform Doped With Eu(dbm) 3 Phenmentioning
confidence: 94%
“…As additives, only lauroylperoxide, as the thermal initiator, and 1-butyl-mercaptan, as the chain transfer reagent, were added to the nitrogen-saturated monomers solution. The combination of lauroylperoxide as the initiator and 1-butyl-mercaptan as the transfer agent is popular for POFs [21,38,39] because lauroylperoxide dissociates to non-gaseous products at mild conditions (t 1/2 = 10 h, 61 • C), thus preventing inclusions or air bubbles in the polymer. The selected ratio from lauroylperoxide to 1-butyl-mercaptan ranging from 0.03 to 0.2 mol % results in the production of polymers with a degree of polymerization, P n , of approximately 900.…”
Section: Monomer Selection and Experimental Setupmentioning
confidence: 99%